Protocol for a scoping review of the evidence concerning the unique needs and experiences of Orthodox Jewish women and their partners using maternity services - Michal Rosie Meroz; Christine McCourt; Carol Rivas (PLoS ONE, 2025)
Background Orthodox Jews follow the Jewish law, Halacha, that determines most daily activities and behaviours. Halacha restrictions and the insular lifestyle of groups within the Orthodox community have led to cultural barriers when interacting with NHS maternity services in the UK. Aims and objectives This protocol describes a scoping review that will aim to: explore the needs of Orthodox Jews when interacting with maternity services and their experiences in the UK; to what extend this topic has been studied; and identify any gaps that need further research. Rationale The literature on this topic is scarce. There is an urgent need to understand the unique needs of these communities in order to make NHS maternity services accessible to all. Methods The scoping review will follow Arksey and O’Malley’s framework for scoping reviews. We will utilise a broad search strategy that will include terms such as Orthodox Jewish, Haredi, Halacha, Needs, Experiences and Maternity Services. We will search the grey literature and databases such as OpenGrey, PubMed, Web of Science, CINHAL, SocINDEX and ProQuest. The search will be an iterative process that will be led by the search itself and the Patient and Public Involvement (PPI) work done in parallel. Inclusion criteria Using the terms above, we will include English papers from all OECD countries, applying no restrictions on publication year. Expected outcomes Mapping the literature will allow a better understanding of the needs and experiences of the Orthodox community when interacting with NHS maternity services in the UK and will lead to the next stage of the project that aims to make these services more culturally sensitive.